Kas yra politika? - Jokubaitis, Alvydas (Problems / Problemos)
The division of political scientists into philosophers and sociologists is an important factor behind their inability to understand politics. Sociologists are incapable of grasping the whole, philosophers are bad at understanding particularities. The aim of the paper is to show the inadequacy of both of these forms of knowledge. Immanuel Kant’s conception of aesthetic judgement allows us to gain a better understanding of politics. Hannah Arendt attempted to explain Kant’s Critique of Judgment as an important treatise for political philosophy. The power of judgement opens up a broad horizon for our imagination. Ideas can be associated with various different appearances and this is why reliable theoretical definition of politics is impossible. It is impossible to ascribe an adequate object of experience to the idea of politics and for this very reason various substitutes are used. The formation of these substitutes corresponds to the requirements of the power of judgement that connects universality to particularity. The analysis of the aesthetic judgement reveals why attempts to define politics face unsolvable difficulties. Philosophers and sociologists attempt to gain a theoretical understanding of an object which belongs to the realm of aesthetic judgement. The article does not provide an answer to the problem of definition of politics, it shows why such a definition is impossible.